Hydrogen donors and acceptors and basic amino acids jointly contribute to carcinogenesis. (January 2017) - Tang, Man; Zhou, Yanchao; Li, Yiqi; Zou, Juntong; Yang, Beicheng; Cai, Li; Zhang, Xuelan; Liu, Qiuyun
Abstract: A hypothesis is postulated that high content of hydrogen donors and acceptors, and basic amino acids cause the intracellular trapping of the H + and Cl − ions, which increases cancer risks as local formation of HCl is mutagenic to DNA. Other cations such as Ca 2+, and weak acids such as short-chain organic acids may attenuate the intracellular gathering of the H + and Cl −, two of the most abundant ions in the cells. Current data on increased cancer risks in diabetic and obese patients are consistent with the assumption that hydrogen bonding propensity on glucose, triglycerides and other molecules is among the causative factors.